ANALISIS TECHNOLOGY ACCEPTANCE MODEL PADA PENGGUNA DOMPET DIGITAL DI DAERAH ISTIMEWA YOGYAKARTA - Adhi Prakosa; Ahsan Sumantika (Jurnal Manajemen, 2020)
TAM is a model that uses to see the outcomes and reactions of someone in using technology. In this study, researchers used the TAM model to investigate intentions to use digital wallet services. Perceived ease of use, perceived usefulness, risk, and trust as independent variables, while the intention variable as the dependent variable. The study was conducted in the Daerah Istimewa Yogyakarta, using 72 samples of respondents OVO digital wallet. Hypothesis testing using multiple linear regression analysis. The results of this study are perceived ease of use and perceived usefulness positive and significant effect of intention to use a digital wallet, while risk and trust factors are not related to intention to use a digital wallet. Keyword: perceived ease of use, perceived usefulness, risk, trust, intention to use, OVO digital wallet